Autologous Haematopoietic Stem Cell Transplantation (AHSCT) in Severe Crohn's Disease: A Review on Behalf of ECCO and EBMT. (8th January 2018) - Snowden, John A; Panés, Julián; Alexander, Tobias; Allez, Matthieu; Ardizzone, Sandro; Dierickx, Daan; Finke, Jürgen; Hasselblatt, Peter; Hawkey, Chris; Kazmi, Majid; Lindsay, James O; Onida, Francesco; et al.
Abstract: Despite the major recent progress in the treatment of Crohn's disease [CD], there is a subset of patients in whom the disease runs an aggressive course with progressive tissue damage requiring early and repeated surgical management. Increasing evidence supports sustained and profound improvement in gastrointestinal parameters and quality of life following high-dose immunosuppressive therapy and autologous haematopoietic stem cell transplantation [AHSCT] compared to standard therapy in this context. In addition, international transplant registry data reflect the use of AHSCT in CD outside of trials in selected patients. However, AHSCT may be associated with significant treatment-related complications with risk of transplant-related mortality. In a joint initiative, the European Crohn's and Colitis Organisation [ECCO] and the European Society for Blood and Marrow Transplantation [EBMT] have produced a state-of-the-art review of the rationale, evaluation, patient selection, stem cell mobilization and transplant procedures and long-term follow up. Given the unique spectrum of issues, we recommend that AHSCT should only be performed in experienced centres with expertise in both haematological and gastroenterological aspects of the procedure. Where possible, patients should be enrolled on clinical trials and data registered centrally. Future development should be coordinated at both national and international levels.